Borderlines: Essays on Mapping and The Logic of Place - Abeliovich, Ruthie (De Gruyter, 2019)
Borderlines innovatively explores the ways artistic interventions construct social, cultural, and mental spaces. The fifteen essays bring a broad multidisciplinary approach to the concept of borderlines and its markings through artistic manifestations. Rejecting older "normative" understandings of the word border lines as signifying semantic irreversibility, this work gives prominence to the plasticity of the combined single word "borderlines." Borderlines is a collection of essays that address the cultural, artistic, conceptual, and performative mapping of places. The essays in this collection "write" borderlines from a wide variety of perspectives, representing diverse disciplines, cultural backgrounds, countries, and generations. It presents the pervasiveness of borderlines as an intellectual, artistic and political concept, across media, theories, and places. Borderlines is intended for academic specialists and students in cultural studies, theatre and performance, media and sound studies. Author information: Ruthie Abeliovich, The University of Haifa. Edwin Seroussi, The Hebrew University of Jerusalem.